2001
DOI: 10.1097/00019605-200104000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in Patau syndrome

Abstract: A female patient with an extra chromosome 13 (Patau syndrome) is described. There are only five previous reports of patients with trisomy 13 who have survived past the first decade. It is concluded that non-lethal congenital anomalies and aggressive medical care play an important role in the survival of patients with trisomy 13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 4 publications
3
27
0
2
Order By: Relevance
“…The same study showed that females with trisomy 13 have a higher survival rate than male patients. Another study proposed that the presence of non-lethal congenital anomalies and the aggressive medical care may contribute positively to the long survival of trisomy 13 patients [Tunca et al, 2001]. We believe that the long survival in our case is possibly due to the absence of holoprosencephaly and cardiac malformations.…”
Section: To the Editormentioning
confidence: 55%
See 2 more Smart Citations
“…The same study showed that females with trisomy 13 have a higher survival rate than male patients. Another study proposed that the presence of non-lethal congenital anomalies and the aggressive medical care may contribute positively to the long survival of trisomy 13 patients [Tunca et al, 2001]. We believe that the long survival in our case is possibly due to the absence of holoprosencephaly and cardiac malformations.…”
Section: To the Editormentioning
confidence: 55%
“…Trisomy 13 is characterized by multiple malformations of the cardiac, central nervous, and urogenital systems [Phatak et al, 2004]. There have only been five cases of patients with trisomy 13 previously reported, who had survived past the first decade [Redheendran et al, 1981;Singh, 1990;Zoll et al, 1993;Tunca et al, 2001]. In this report, we present a newborn with trisomy 13, the fourth longest described in the literature and the longest survival (146 months) reported in Greece.…”
Section: To the Editormentioning
confidence: 76%
See 1 more Smart Citation
“…We have fully documented the clinical features of our patient in comparison to all other full trisomy 13 reported cases over the age of 5 years old (table 1).
Learning points It has been speculated that aggressive medical care may play a role in the increasing life expectancy of patients with trisomy 13 9. Conversely, Rasmussen et al 5 have suggested that the average life expectancy of the trisomy 13 patient population has decreased over time, and that this may be due to less aggressive medical care provided as clinicians become increasingly aware of the poor prognosis.
…”
Section: Discussionmentioning
confidence: 99%
“…A case of trisomy 13 with long-term survival (>27 years) who also had hyperpigmented areas but no evidence of mosaicism in blood lymphocytes or skin fibroblasts has been published. The prolonged survival was attributed to nonlethal congenital anomalies and aggressive medical care [Tunca et al, 2001]. However, the senior author follows a patient with full regular trisomy 13 currently in his mid-twenties [Lacassie, unpublished work].…”
mentioning
confidence: 99%